L'émergence des chanteurs immigrants sur la scène de la musique populaire au Québec : l'exemple de Corneille et de Lynda Thalie - Proulx, Robert (Quebec Studies, 2008)
A l'instar des ecrivains de la litterature migrante, des chanteurs et des chanteuses venus de divers pays ont fait du Quebec leur port d'attache et le foyer de leur carriere artistique. Ce phenomene assez recent a fait qu'au cours des dix dernieres annees on a vu debarquer au Quebec des artistes d'Hai'ti, du Bresil, du Mexique, du Maroc, du Rwanda, du Tchad, de l'Algerie, et du Venezuela, chacun avec sa musique, sa couleur, et sa sensibilite propre. Dans cette nouvelle branche de la chanson quebecoise on trouve les themes de predilection de la litterature migrante tels que l'exil, la nostalgie, le sentiment de perte, l'adaptation a un nouveau pays, l'integration, le racisme, la xenophobie, et l'hospitalite. La chanson quebecoise s'enrichit de ces differents apports; car ces artistes apportent avec eux non seulement des voix, des sons et des styles musicaux nouveaux, mais aussi des themes inedits et des trames narratives originales qui refletent leur culture d'origine, leur passe, et leurs valeurs de meme que leurs emotions liees a leurs defis actueis et a leurs reves pour l'avenir. (1) Dans cet article, nous examinerons en detail l'ceuvre de deux d'entre eux: Lynda Thalie qui, selon Monique Giroux, l'experte en chanson francophone de Radio-Canada, "est, parmi les artistes neo-quebecois, celle qui a pris le plus de place et est la plus susceptible de conquerir un large public" (cite par Vignaux) et Corneille, celui qui a jusqu'a ce jour remporte le plus grand succes aussi bien commercial que d'estime. II a vendu plus d'un million et demi de ses deux premiers disques, et a lance son premier disque en anglais, "The Birth of Cornelius," au Japon en mai 2007. (2) Lynda Thalie: l'exilee d'Algerie

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

The Ladino Song in the 20th Century: A Study of the Collections of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Université Bar-Ilan, 2007)
Keywords: Pas de lien web

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

The Memoirs of a Partisan from Salonika - Melammed, Renee Levine (Nashim: A Journal of Jewish Women's Studies & Gender Issues, 2004)